Integrated renewable H2 production and industrial wastewater treatment using a semi-pilot scale flow electrolyzer - Sgarbi, Ricardo; Mandelli, Cecília Montanha; Ruotolo, Luis Augusto Martins (Universidade Federal de São Carlos, 2025)
Integration of mandatory wastewater treatment with renewable H2 production has been explored as a cost-reduction strategy, by trading the generated H2 as feedstock to relevant industries. A semi-pilot scale flow electrolyzer, innovatively designed for this purpose, demonstrated promising performance. Both the cathodic hydrogen evolution reaction and the anodic organic electrooxidation were investigated under two sets of operational conditions: (i) temperature, current density, and conductivity, and (ii) membrane type, and catholyte concentration. Thereupon, it is observed that a highly conductive, alkalinized catholyte, in combination with a low-cost anion exchange membrane, enhances both reactions by amplifying conductivity, promoting OH– ion transport, and accelerating anode kinetics. Furthermore, the electrolyzer successfully treated industrial wastewater while simultaneously producing renewable H2 with low CO2 emissions: 2.0 kgCO2 kgH2-1. The overall process cost was mainly influenced by electricity prices, ranging from 2.7 to 15.7 US$ kgH2-1 under optimized conditions.
Keywords: Green hydrogen production; Electrochemical reactor; Kinetics; Phenol electrooxidation; Real effluent; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA